Limosilactobacillus fermentum JL-3 isolated from "Jiangshui" ameliorates hyperuricemia by degrading uric acid. (1st January 2021) - Wu, Ying; Ye, Ze; Feng, Pengya; Li, Rong; Chen, Xiao; Tian, Xiaozhu; Han, Rong; Kakade, Apurva; Liu, Pu; Li, Xiangkai
ABSTRACT: Recent studies into the beneficial effects of fermented foods have shown that this class of foods are effective in managing hyperuricemia and gout. In this study, the uric acid (UA) degradation ability of Limosilactobacillus fermentum JL-3 strain, isolated from "Jiangshui" (a fermented Chinese food), was investigated. In vitro results showed that JL-3 strain exhibited high degradation capacity and selectivity toward UA. After oral administration to mice for 15 days, JL-3 colonization was continuously detected in the feces of mice. The UA level in urine of mice fed with JL-3 was similar with the control group mice. And the serum UA level of the former was significantly lower (31.3%) than in the control, further confirmed the UA-lowering effect of JL-3 strain. Limosilactobacillus fermentum JL-3 strain also restored some of the inflammatory markers and oxidative stress indicators (IL-1β, MDA, CRE, blood urea nitrogen) related to hyperuricemia, while the gut microbial diversity results showed that JL-3 could regulate gut microbiota dysbiosis caused by hyperuricemia. Therefore, the probiotic Limosilactobacillus fermentum JL-3 strain is effective in lowering UA levels in mice and could be used as a therapeutic adjunct agent in treating hyperuricemia.